2021
DOI: 10.1186/s43141-021-00167-6
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic and anti-inflammatory potential of Lupeol isolated from Indian traditional medicinal plant Crateva adansonii screened through in vivo and in silico approaches

Abstract: Background Lupeol, a triterpene bioactive compound isolated from Indian traditional plant Crateva adansonii acted as promising and alternative anti-inflammatory agent to treatments of diseases related to inflammation. The inflammatory process in the body serves an important function in the control and repair of injury. However, it is self-perpetuating in number of disease conditions, which must be prevented and treated. Worldwide most prescribing NASID drug shows severe side effects. Whereas dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…This lowers the infiltration macrophage to damaged tissues, hence reducing inflammation. [ 39 ]. It also chelates toxins such as heavy metal ions [ 40 ] Stimulates the production, and migration of keratinocytes and fibroblasts to injured tissues, by activating the PI3K-PKB/Akt and p38/ERK/MAPK pathways [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This lowers the infiltration macrophage to damaged tissues, hence reducing inflammation. [ 39 ]. It also chelates toxins such as heavy metal ions [ 40 ] Stimulates the production, and migration of keratinocytes and fibroblasts to injured tissues, by activating the PI3K-PKB/Akt and p38/ERK/MAPK pathways [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…This lowers the infiltration macrophage to damaged tissues, hence reducing inflammation. [ 39 ]. It also chelates toxins such as heavy metal ions [ 40 ]…”
Section: Resultsmentioning
confidence: 99%
“… 62 Besides, COX-II responsible for the production of PGE2, NO and MMP-9 is also upregulated. 63 Moreover, the MMPs are a series of proteolytic enzymes (especially MMP-9 produced by monocytes) that downregulate the ECM synthesis and their biological activities are controlled by TIMP-1 (tissue inhibitor of metalloproteinase), where the imbalance in MMPs / TIMPs ratio is critical in the OA progression. 61 NF-κB is one of the inflammatory cytokine-induced transcription factors that regulate the expression of iNOS, COX-II, TNF-α, IL-6, MMPs and other cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indeed showed that LPL with a significant reduction in ROS/RNS generation and recovering the depleted glutathione level resulted in lower TNF-α and hepatic functional enzymes production, confirming its antioxidant and anti-inflammatory effects and also its medicinal use in the treatment of both disorders. The anti-inflammatory effect of LPL on carrageenan-induced acute inflammation in rodents and also on macrophage pro-inflammatory phenotype reduction in vitro model have been recently documented ( 36 37 ). There are also reports supporting the fact that mitochondria-targeted antioxidant, which is so-called Mito-Q10, with reduction of experimentally-induced PCOS injuries including elevated HOMA-IR and MDA levels and reduced glutathione content, was able to decline the mitochondria-mediated apoptotic cell death in the ovary ( 38 ).…”
Section: Discussionmentioning
confidence: 99%